Efforts to Prevent Acts of Abuse Authority That Result in Harm State Finances Using the Government’s Internal Supervision Apparatus - Santoso , Bagus Teguh; Munir, Ahmad (Fakultas Hukum Universitas Widya Mataram, 2023)
Law enforcers are trapped in the legal mechanism along with the punishment criteria determined by the legislators, for that reason our positive law has been regulated which is far from and contrary to the objective of a just law. The presence of excessive criminalization/criminalization with various kinds and types of negative law enforcement behavior in determining the criminal process, makes criminalization ultimately have a negative meaning and has the potential to hinder the development process. The research method used in this research is normative legal research with a statutory approach and a conceptual approach to the abuse of authority by internal government apparatus which is detrimental to state finances. The results of this study indicate that the assessment of the Government's Internal Supervisory Apparatus on administrative errors that cause state losses needs to be revised again. Because the assessment of the Government Internal Supervisory Apparatus will be followed up at the State Administrative Court. This is very risky because it is related to the element of causing harm to state finances, in fact it is the authority of the Corruption Court to decide it.